Development of an improved ligand mimetic calibration system for the analysis of iron(III) in seawater using the iron(III) chalcogenide glass ion selective electrode: A combined mechanistic and analytical study - Maric, M.; Sohail, M.; Veder, J.; De Marco, Roland (Elsevier, 2015)
© 2014 Elsevier B.V. All rights reserved. Further to previous work on a seawater ligand mimetic calibration system for the electroanalysis of iron(III) in seawater using the iron chalcogenide glass ion-selective electrode (ISE), this study utilized alternative blends of synthetic ligands, in order to fine-tune and optimize the calibration response characteristics of this sensor for the electroanalysis of free iron(III) in seawater. Herein, an alternative calibration system (ACS) was derived using a mixture of 10-4 M iron(III) chloride, 10-4 M ethylenediaminetetraacetic acid (EDTA), 10-3 M copper(II) sulphate, 5 × 10-3 M ethylenediamine (EN) and 0.60 M sodium chloride yielding a Nernstian response of about 30 mV decade-1. The electroanalysis of free iron(III) in seawater using the ACS generated a free iron(III) level commensurate with the predicted organic and inorganic speciation of iron(III) in seawater. Furthermore, electrochemical impedance spectroscopy (EIS), synchrotron radiation X-ray photoelectron spectroscopy (SR-XPS) and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy have demonstrated that the surface reaction processes of this membrane in the ACS are comparable to those experienced in a natural seawater matrix. Ultimately, this study demonstrated that the ACS can mimic the surface chemistry and concomitant potentiometric response characteristics of the iron(III) sensor in seawater, enabling reliable electroanalyses of free iron(III) in seawater.